P1_1 An Analysis of the Feasibility of a Giant Death Beam - Holt, Nicholas; Murphy, Jeremy; Roberts, Kieran; Tranter, Jemima (Physics Special Topics, 2020)
This paper examines the possibility of constructing a giant beam of the Sun’s radiation to befocused onto the Earth’s surface. The purpose of this was to emanate the weapon of mass de-struction from a James Bond film. Our results reveal that the spherical lens required to generatea beam of cross-sectional area 1m^2 would have a radius of 141m.